Learning Innovation in The Merdeka Curriculum: A Critical Pedagogical Review in Primary Schools - Indriyani, Tri Sila; Abidin, Yunus (International Conference on Elementary Education, 2025)
This study explores learning innovations within the Curriculum Merdeka at State Elementary School 268 Panyileukan, Bandung City, from a critical pedagogical perspective. It aims to understand the innovative practices implemented by teachers and the extent to which values of critical reflection and social awareness are embedded in the learning process. The research employed in-depth interviews, participatory observation, and document analysis conducted from July to October 2025. The findings indicate that Curriculum Merdeka has successfully promoted project-based, differentiated, and contextual learning approaches that enhance students’ creativity and motivation. However, critical pedagogical aspects—such as deep reflection on the learning process and the development of students' critical awareness of social issues—remain underdeveloped. Teachers tend to emphasize evaluation based on final learning products without fully integrating critical thinking throughout the process. Other challenges include limited teacher understanding of the curriculum, insufficient infrastructure support, and the need for ongoing professional development. This study recommends strengthening teacher capacity through training in critical pedagogy, designing projects that connect learning to real-world social issues, and enhancing infrastructural support. This research makes an important contribution to the development of curriculum and teaching practices that are not only technically innovative but also liberating and empowering for students as active learners in real social contexts.